The Occurrence of Psalm 118(117):6 in Hebrews 13:6: Possible Liturgical Origins? - Steyn, Gert J. (Neotestamentica, 2006)
This contribution explores the presence of Ps 118(117) in Hebrews 13. Being part of the Hallel and with its pointers to the Jewish festivals, it possibly points in a liturgical direction. This inevitably raises the question about the Vorlage that the author might have used for his quotation. Looking at the tradition-historical aspects, the text critical aspects and the hermeneutical aspects of the quotation from Ps 118(117):6 within Hebrews 13, the possibilities regarding the MT, the LXX, other possible sources from early Judaism and early Christianity, as well as the option of possible liturgical origins, are being investigated.